2022
DOI: 10.1111/jog.15196
|View full text |Cite
|
Sign up to set email alerts
|

Decreased dysmenorrhea pain in girls by reducing oxidative stress and inflammatory biomarkers following supplementation with oleoylethanolamide: A randomized controlled trial

Abstract: Aim This study aimed to evaluate the oleoylethanolamide (OEA) effects on oxidative stress and inflammatory factors in girls with primary dysmenorrhea. Methods This double‐blind, placebo‐controlled clinical trial was done on population consisted of female students who had dysmenorrhea pain based on the visual analogue scale (VAS) questionnaire. Patients were randomly allocated to groups consuming a capsule containing 125 mg of OEA per day (n = 22) or placebo (n = 22) for 2 months. The severity of the pain, tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Its metabolic potential explains its significance in host health and disease ( 36 , 37 ). Studies have found that the occurrence and development of PD are related to the decrease of human immunity, the increase of inflammatory factors, the abnormal secretion of hormones and other factors, but there are relatively few studies on whether it is related to flora ( 38 , 39 ). The results of this study showed that GWUAP could affect the OTU composition of intestinal flora in PD rats, regulate the diversity of flora, and screen out multiple differential flora related to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Its metabolic potential explains its significance in host health and disease ( 36 , 37 ). Studies have found that the occurrence and development of PD are related to the decrease of human immunity, the increase of inflammatory factors, the abnormal secretion of hormones and other factors, but there are relatively few studies on whether it is related to flora ( 38 , 39 ). The results of this study showed that GWUAP could affect the OTU composition of intestinal flora in PD rats, regulate the diversity of flora, and screen out multiple differential flora related to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of pain during menstruation can be caused by dysmenorrhea which has different levels of pain in each student according to what students feel during menstruation. The psychological impact of dysmenorrhea can be in the form of emotional conflicts, tension, and anxiety (Kazemi, Lalooha, Nooshabadi, & Haghighian, 2022). This can lead to feelings of discomfort and alienation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OEA treatment improves the glycemic index and insulin resistance, and it may be a helpful supplement to control pre-diabetes status [ 102 ]. Moreover, OEA use has been indicated to alleviate dysmenorrhea pain in girls by reducing oxidative stress and inflammatory biomarkers [ 103 ]. Interestingly, OEA therapy influences gut microbiota composition and the expression of intestinal cytokines in Peyer’s patches [ 104 ].…”
Section: Oleoylethanolamidementioning
confidence: 99%